On Student Comprehension For There Year Courses In Mathematics Department - Salim AL-Kutubi , Hadeel; Razzaq AL-Saiq, Inaam (University of Thi-Qar Journal of Science, 2009)
In this paper, we present the significant difference between the level of student comprehension for these year courses and for all student of mathematical department,college of science, Kufa university .Moreover to find out the effect of scientific, personality,ability of evaluation and ability of communication To have the goal ,we used some statistical methods like experimental design,correlation and regression analysis.